Perlindungan Hukum Data Pribadi Konsumen Dalam Perjanjian Pinjaman Online Di Indonesia - Puspita, Khafidah (State of Islamic Institute Langsa, 2023)
Online loans make it easy to complete the entire loan process. Starting from initial qualification to loan financing. Online loan providers provide convenience in borrowing online because they offer lower interest rates. Even though the fact that happened has a risk for data dissemination due to a lack of forms of personal data protection. So with this matter the publication of Law Number 27 of 2022 Concerning Personal Data Protection, with the existence of the Personal Data Protection Act, the public is expected to be careful in taking action. And strengthened by the issuance of OJK regulations, POJK NO. 10/POJK.05/2022 Concerning Information Technology-Based Joint Funding Services. This article uses normative legal research methods with regard to empirical legal research. The results of the study found that the protection of consumer personal data in online loans must be highly protected and if consumer data is available it will be carried out in court with certain trials and very high criminal provisions. Second: online loan arrangements in Indonesia have been updated by the OJK in a very strict and serious manner. So with this the author urges the OJK not to be cheated on new companies to establish online loans